Inter-Agency Conflict and its Implication on National Security in Nigeria - Abioye, Oyeyemi Olufemi; Alao, David Oladimeji (NIU Journal of Social Sciences, 2020)
Violent conflict is gradually becoming one of the defining characteristics of Nigeria. The problem of violence conflict in Nigeria has become more worrisome as the security operatives whose duty is to maintain peace, detect and suppress crimes have themselves become engulfed in violent conflicts, thereby giving criminals opportunity to unleash terror on the citizenry with impunity. Also, unethical conducts are held accountable for inter-agency conflict, superiority struggles, jurisdictional boundaries as well as role conflict arising from operational duties. To this end, repeated violent clashes among these security professionals have consistently alienated them from the public. This situation has further caused loss of confidence and respect from the citizenry. This paper therefore reviews the challenges of inter-agency conflict that negatively impact on national security. The paper adopted exploratory research design and relied on qualitative data, while the population comprised of security agencies particularly the Police and Nigeria Security and Civil Defence Corps operatives as study population. Data collected from secondary sources are relevant books, journals, publications from website of security agencies and internet materials. The paper concluded that there is need for inter-agency collaboration or cooperation in addressing inter-agency conflict as well as promoting national security in Nigeria. Keywords : Security, Inter-agency, Conflict, National security, Collaboration.